2007
DOI: 10.1177/154405910708600714
|View full text |Cite
|
Sign up to set email alerts
|

Gel Phase Formation at Resin-modified Glass-ionomer/Tooth Interfaces

Abstract: Ionic bonding between polyalkenoic acid and hydroxyapatite may explain the excellent bonding retention of glass-ionomers in clinical trials. We have here investigated the extent to which the self-adhesiveness of resin-modified glass-ionomers (RMGIs) can be attributed to this chemical bonding capacity. Therefore, the interaction of 3 RMGIs with tooth substrates was comprehensively characterized, with electron and atomic force microscopy correlated with x-ray photoelectron spectroscopy (XPS). Interfacial ultrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 15 publications
1
66
0
8
Order By: Relevance
“…The selfadhesive bonding mechanism of these materials is twofold: (1) the ionic bonding to hydroxyapatite around collagen, as in conventional GIC, and (2) the micromechanical interlocking for those resinmodified GIC that additionally hybridize dentin. 22 For Vitrebond, the first material to contain the copolymer used in EB and SB, there is no evidence of the second mechanism (ie, hybridization or gel phase deposition). 22 Since the bonding associated with Vitrebond is stable and there is an tight contact between this material and dentin, chemical interaction is the primary bonding mechanism for this resin-modified GIC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selfadhesive bonding mechanism of these materials is twofold: (1) the ionic bonding to hydroxyapatite around collagen, as in conventional GIC, and (2) the micromechanical interlocking for those resinmodified GIC that additionally hybridize dentin. 22 For Vitrebond, the first material to contain the copolymer used in EB and SB, there is no evidence of the second mechanism (ie, hybridization or gel phase deposition). 22 Since the bonding associated with Vitrebond is stable and there is an tight contact between this material and dentin, chemical interaction is the primary bonding mechanism for this resin-modified GIC.…”
Section: Discussionmentioning
confidence: 99%
“…22 For Vitrebond, the first material to contain the copolymer used in EB and SB, there is no evidence of the second mechanism (ie, hybridization or gel phase deposition). 22 Since the bonding associated with Vitrebond is stable and there is an tight contact between this material and dentin, chemical interaction is the primary bonding mechanism for this resin-modified GIC. 22 A five-year clinical study 23 with a CP-containing resin-modified GIC material reported excellent retention rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…micro-mechanical and chemical adhesion) closely resembles that of glass-ionomers. 62 The additional chemical bonding of mild self-etch adhesives and glass-ionomers is supposed to be beneficial in terms of bonding durability. 18,20 However, the ability to chemically bond to HAp is not sufficient on its own.…”
Section: Chemical Bondingmentioning
confidence: 99%